EARLY EVOLUTION OF THE EARTH AND MOON: NEW CONSTRAINTS FROM HF-W ISOTOPE GEOCHEMISTRY - Halliday A.; Rehkamper M.; Der-Chuen L.; Wen Y. (My University, 1996)
The W isotopic composition of the bulk silicate Earth (BSE) is chondritic within current analytical uncertainties, indicating that terrestrial core formation commenced more than 50 Myr after the differentiation of the earliest planetesimals in the solar system. This is consistent with U-Pb data and holds true whether core formation is modelled as a single catastrophic event or as a continuous process that started late, unless accretion was more than about twice as slow as recently estimated. The chondritic W isotopic composition of the BSE provides support for the assumption that the overall lithophile/siderophile refractory element ratio of the Earth is close to chondritic, but requires mixing to remove early heterogeneities introduced by the accretion of any planetesimals already segregated into silicate and metallic portions with distinct W isotopic compositions. The same applies to any later accreted material, such as the putative Moon-forming giant impactor. Many models of terrestrial accretion and core formation involve a core that developed during the first 90% of accretion history, generally considered to correspond to a time span significantly shorter than that permitted by the W isotopic data. These models are difficult to reconcile with the W isotopic data unless the proto-Earth was re-homogenized by a major impactor, or accretion took longer than currently estimated. The W isotopic compositions of early lunar rocks provide the best hope of determining which model of accretion and core formation is correct for the Earth. A conservative assessment of isotopic ages for lunar highlands rocks, combined with the constraints from W isotopic data, indicate that the onset of major terrestrial core segregation, the formation of the Moon and the development of a lunar magma ocean all took place within < 80 Myr at 4.47 +/- 0.04 Ga. Certain isotopic ages for lunar rocks would be consistent with a more restricted time window of 4.50 +/- 0.01 Ga. Potassium and Cr isotopic data indicate early volatile depletion of the material from which the Earth and Moon formed and constrain models of pre-core Pb isotopic evolution. The various estimates for the Pb isotopic composition of the BSE seem best explained by strong U/Pb fractionation accompanying terrestrial core formation. Using the 4.47 +/- 0.04 Ga age of the core, the second stage Pb isotopic evolution reproduces reasonable estimates for the present day BSE Pb isotopic composition if the second stage 238U204Pb (μ) is in the range of 8.9 +/- 0.5. The 'lead paradox' is entirely predictable from the 4.47 +/- 0.04 Ga age of the core. The similarities between the late ages of the Earth's core, the Moon and the degassing of Xe from the terrestrial mantle are consistent with an accretion history which is more protracted than currently modelled. Alternatively, late impacts may have triggered all of these events. If a single late impact is invoked as an explanation, the Moon must have been derived primarily from the silicate portion of the impactor. Otherwise, the Hf-W data may define the age of a core that formed as a result of another impact, shortly prior to that which formed the Moon.
Keywords: EARTH-MOON COUPLE; DIFFERENTIATION; GEOCHEMISTRY; HAFNIUM; TUNGSTEN; U-PB